Pengaruh Tenaga Kerja Dan Pengeluaran Pemerintah Terhadap Pertumbhan Ekonomi Di Kabupaten Pakpak Bharat - Alkursi Bancin (Politeknik Siber Cerdika Internasional, 2023)
This study aims to determine the effect of labor and government spending on economic growth in Pakpak Bharat Regency from 2011 to 2020. The research method used is a quantitative approach. The research objectives include knowing the effect of the influence of labor on economic growth, the effect of government spending on economic growth and the influence of labor and government spending simultaneously on economic growth in Pakpak Bharat Regency. Based on the research conducted, the results and conclusions are as follows: first, that labor has a positive and significant effect on economic growth in Pakpak Bharat district, and government spending has a positive and insignificant effect on economic growth in Pakpak Bharat Regency, third simultaneously labor and expenditure the government has a significant effect on economic growth in Pakpak Bharat Regency, with an R Square value of 0.774507 meaning that the variable of labor and government expenditure affects the economic growth of Pakpak Bharat Regency by 77.45% while the remaining 0.2255% economic growth of Pakpak Bharat Regency is influenced by factors other.